Investigating the Efficacy of Ginger and Lemon Boiled Water: A New Approach to Treating Mild Hyperemesis Gravidarum in Pregnant Women - Evitasari, Desi; Amalia, Merlly; Suyanti, Suyanti; Listiani, Imas; Purnamasari, Devi; Po Yuan Wang; Juan Anthonio (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2024)
In a quasi-experimental study, we investigated the impact of ginger and lemon boiled water on level 1 hyperemesis gravidarum in pregnant women. Utilizing a one-group pretest-posttest design, the study involved 20 participants who reported experiencing severe hyperemesis gravidarum symptoms. Following the intervention, the incidence of severe symptoms was reduced to zero among the participants. Statistical analysis with the Wilcoxon signed-rank test revealed a significant reduction in symptoms (p=0.001), indicating the potential of ginger and lemon boiled water as an effective non-pharmacological remedy for nausea and vomiting in pregnancy. These results advocate for the inclusion of alternative therapies in health education for pregnant women and highlight the necessity of seeking professional healthcare advice when experiencing such symptoms.